2021
DOI: 10.1177/23259671211005091
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the Predictors of Functional Outcomes After Arthroscopic Rotator Cuff Repair Modified Frailty Index, Clinical Frailty Scale, and Charlson Comorbidity Index

Abstract: Background: The incidence of rotator cuff tears increases with age, and operative management is usually required in patients with persistent symptoms. Although several studies have analyzed the effect of age and comorbidities on outcomes after rotator cuff repair, no study has specifically examined the consequence of frailty. Purpose: To determine the best frailty/comorbidity index for predicting functional outcomes after arthroscopic rotator cuff repair. Study Design: Cohort study; Level of evidence, 3. Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…One might expect that pre-operative assessment scores would be inversely related to post-operative outcomes; that is, that higher pain and lower functional scores pre-operatively would predict worse post-operative outcomes. Likewise, several studies demonstrate this to be the case [ 25 , 26 , 27 , 28 ]. Conversely, we found lower pre-operative ASES and VAP scores to be the most significant predictors of post-operative ASES score improvement, with higher pre-operative values negatively influencing post-operative scores.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…One might expect that pre-operative assessment scores would be inversely related to post-operative outcomes; that is, that higher pain and lower functional scores pre-operatively would predict worse post-operative outcomes. Likewise, several studies demonstrate this to be the case [ 25 , 26 , 27 , 28 ]. Conversely, we found lower pre-operative ASES and VAP scores to be the most significant predictors of post-operative ASES score improvement, with higher pre-operative values negatively influencing post-operative scores.…”
Section: Discussionmentioning
confidence: 83%
“…Our results did not demonstrate a strong association between gender and post-operative ASES scores, another area of conflicting findings in the literature. Several studies show female sex to be associated with worse post-operative quality of life, mental health, pain, and functional assessments [ 26 , 27 , 48 , 49 , 50 , 51 ]. Conversely, other studies demonstrate that gender does not influence post-operative outcomes [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6] Frailty is described as deterioration in physiological functioning beyond that attributable to age-related changes alone and has been found to be a more robust predictor of surgical outcomes than American Society of Anesthesiology (ASA) class and age in several studies. [7][8][9][10] There have been 2 main methods of assessing frailty, either operationalizing frailty as the number of comorbidities an individual has in the frailty index model or considering frailty as a syndrome manifested by motor symptoms and unintentional weight loss in the frailty phenotype model. [11][12][13] Several studies have demonstrated that the frailty index can better define the risk of adverse outcomes than the frailty phenotype model.…”
Section: Introductionmentioning
confidence: 99%
“…The mFI-5 may be the newest iteration of a surgical risk proxy, but the question remains as to how its accuracy compares to the use of other single-item proxies such as age, 20 body mass index (BMI), 21 smoking status, 9 comorbidities, 20 ASA class, 22 and other recent risk proxies such as the Modified Charlson Comorbidity Index (mCCI). 23,24 Thus, the purpose of the present study is twofold: first, to evaluate if the mFI-5 can accurately forecast 30-day complication rates in HWSR using the American College of Surgeons' National Surgical Quality Improvement Program (ACS-NSQIP) database. Second, to see how the mFI-5 compares to previously established proxies of surgical risk.…”
Section: Introductionmentioning
confidence: 99%